The functional aspect of linguistic sexism in the Ukrainian mass media - Stafiichuk , Daryna (Current issues of Ukrainian linguistics: theory and practice, 2022)
The purpose of this study is to actualize a concept of "linguistic sexism" in the media discourse through the prism of gender linguistics, which today determines some tendencies in scientific research of modern humanitarian studies. The development of a new political system, the progress of information space, the transformation of the socio-political situation in the country, the emergence of new threats in a rapidly changing world require the development of gender construct in rhetorical theory. An integral part of the modern space is the principle of gender equality, gender democracy and the establishment of gender culture in the world, that is directly implemented into the language. Accordingly, the achievements of gender linguistics study in the media-linguistic aspect significantly affects the formation of moral and material values of modern society. Representation of gender-oriented topics in the language of the media contributes to their public discussion and in the future to overcoming stereotypes in society in the future. The extra- and intralingual motivation of the spread мені не нравиця це спред може wide usage of linguistic sexism in the media discourse was analyzed. Special attention is paid to the concept of "linguistic androcentrism" as a manifestation of linguistic sexism through the prism of domestic and global gender studies on the example of informational media texts. The article analyzes the texts of informational resources of well-known Ukrainian media in order to determine the selection and functioning of a complex of linguistic means of various expressions of linguistic sexism in mass media. Our study also examines the concept of "gender metaphor", its functions and expressions in the language of the Ukrainian mass media. In addition, the article describes ways of avoiding linguistic sexism in the discourse media communication and identifies prospects of further research in a comparative context using particular examples.